1998
DOI: 10.1002/(sici)1521-4141(199801)28:01<1::aid-immu1>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of two members of the SIRPα family of protein tyrosine phosphatase binding proteins in cattle that are expressed on monocytes and a subpopulation of dendritic cells and which mediate binding to CD4 T cells

Abstract: Recent experimental studies have greatly clarified the function of cell surface molecules in the induction and modulation of T cell responses by antigen-presenting cells (APC). However, the differences in ability to stimulate T cells evident for different types and subpopulations of the same APC, such as dendritic cell subsets, is less well understood. This report details an investigation of an antigen expressed on monocytes that is also expressed on a subset of cattle afferent lymph veiled cells (ALVC). A cDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

1998
1998
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(51 citation statements)
references
References 36 publications
2
48
1
Order By: Relevance
“…Support for this notion was provided by an earlier report in which purified p94, a brain antigen later found to be SHPS-1 (19), promoted neurite outgrowth when added to neuronal cell cultures (23). Moreover, it was recently observed that SHPS-1 on bovine monocytes interacted with a yet undetermined ligand on CD4 ϩ T-cells, thus improving antigen presentation (20).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Support for this notion was provided by an earlier report in which purified p94, a brain antigen later found to be SHPS-1 (19), promoted neurite outgrowth when added to neuronal cell cultures (23). Moreover, it was recently observed that SHPS-1 on bovine monocytes interacted with a yet undetermined ligand on CD4 ϩ T-cells, thus improving antigen presentation (20).…”
Section: Discussionmentioning
confidence: 91%
“…Whereas other studies are needed to elucidate the distribution of SHPS-1 in hemopoietic cells other than macrophages, recent data on the expression of SHPS-1 in bovine tissues provide further clarification (20). Brooke et al (20) found that a bovine hemopoietic cell antigen previously termed MyD-1 was actually SHPS-1.…”
Section: Discussionmentioning
confidence: 99%
“…The human CD47 mAb B6H12 used in the former study recognizes the same epitope as BRIC126 [28] which inhibited the binding of purified SIRP to purified CD47. Soluble CD47 mAb inhibited T cell proliferation in a MLR [29] and in complementary experiments, a SIRP mAb blocked antigen-specific T cell proliferation by monocytes [5]. Correlation between SIRP expression and the capacity of APC to stimulate an MLR provides corroborative evidence for SIRP/CD47 engagement promoting T cell activation [30].…”
Section: Discussionmentioning
confidence: 98%
“…The SIRP h subtype has an apparent molecular weight of between 85 and 90 kDa in humans and rats and 110-120 kDa in the mouse. Several groups have discovered a SIRP h-like molecule which has been designated SHPS-1, p84, BIT, MFR, MyD-1 and SIRP h 1 [1,[13][14][15][16][17][18]. For simplicity, all these molecules will be referred to here as SIRP h. SIRP hs are extensively glycosylated and have either three or one immunoglobulin (Ig)-like domains.…”
Section: Structural Characteristicsmentioning
confidence: 99%
“…These two transcripts probably reflect the two known variants generated by alternative splicing. SIRP h protein is highly expressed in myeloid cells [17,22,42]. Macrophages may constitute a useful experimental system because they express a single SIRP h far more predominantly than other members [16,31,42,57,58].…”
Section: Distribution Of Sirps Among Tissue and Cell Typesmentioning
confidence: 99%